A study on thermal management in electronic packaging components - Awang Masri, A.A (Universiti Malaysia Sarawak , (UNIMAS), 2002)
Thermal Management (TM) is the most important protection of the Integrated Circuit (IC) and electronic component. TM is one of the keys that has been purposes to the electronic packaging to cool and maintain the integrated circuit and electronic component.